Ensino de jornalismo: perfil profissional, regionalização das habilidades técnicas e competências - Rocha, Eleni Oliveira; Campos, Pedro Celso [UNESP] (My University, 2011)
From 2002 on, when the curricular flexibility was ruled by the Education Ministry, the courses of Journalism in Brazil, more dedicated to improve teaching quality, have tried to adapt its curricular program schedules to regional realities. In this article, they aim to show how Journalism teaching is being provided in the Country and, at the same time, what students think of the disciplines and what do specialists and the press expect from them.

A partir de 2002, quando foi regulamentada a flexibilização curricular pelo Ministério da Educação, os cursos de Jornalismo no Brasil, mais empenhados na melhoria da qualidade do ensino, têm procurado adaptar suas grades curriculares à realidade regional. Neste artigo, tenta-se mostrar como está o ensino de Jornalismo no País e, paralelamente, o que pensam os estudantes sobre as disciplinas, e o que os especialistas da mídia esperam deles
Teaching of journalism: professional profile, regionalisation of technical skills and competences
Keywords: Teaching; Journalism; Profile; Journalist; Disciplines; Ensino; Jornalismo; Perfil; Jornalista; Disciplinas